Design of Intravenous Fluid Monitoring in Inpatients Based on Internet of Things (IoT) - Riski Yulianto; Sumarno (Procedia of Engineering and Life Science, 2022)
Infusion is a medical device that is used to replace lost body fluids or nutrients in some emergency or urgent situations, such as in patients who are dehydrated, unable to digest food by mouth, replaced by intravenous fluids, as for some disorders that usually occur such as blockage of fluids that cause effects. The type of research used is quantitative research with experimental methods. Methods of data collection using the method of observation, interviews, and literature study. The data source of this research uses the Research Library. The data processing methods of this research are reduction and coding. The analysis used is quantitative data analysis. The system built can make it easier for medical users to control infusion fluids in real time (24 hours). The results of this study are sending data every 10-12 seconds, and auto refresh on the blynk application every 5 seconds with a measurement error percentage of 2.25 from the results of manual measurements and sending notifications to smartphones if the volume of infusion fluid is below 6 MM as much as 70x. So that in this prototype the data sharing process was successfully carried out because the ultrasonic data and the temperature of Mlx90614 for infusion fluids were successfully stored in the Blynk database via Arduino Wemos D1R2.